The oxygen reduction reaction in solid oxide fuel cells: From kinetic parameters measurements to electrode design - Ascolani Yael, Julian Esteban (2020)
The research and development of new Solid Oxide Fuel Cell cathode materials is an area of intense activity. The kinetic coefficients describing the O2-reduction mechanism are the O-ion diffusion (Dchem) and the O-surface exchange coefficients (kchem). These parameters are strongly dependent on the nature of the material, both on its bulk and surface atomic and electronic structures. This review discusses the method for obtaining the kinetic coefficients through the combination of electrochemical impedance spectroscopy with focused ion-beam 3D tomography measurements on porous electrodes (3DT-EIS). The data, together with oxygen non-stoichiometry thermodynamic data, is analysed using the Adler-Lane-Steele model for macro-homogeneous porous electrodes. The results for different families of oxides are compared: single- and double-layered perovskites with O-vacancies defects, based on La-Sr cobalt ferrites (La0.6Sr0.4Co1-xFexO3-δ, x = 0.2 and 0.8) and La/Pr-Ba cobaltites (La0.5-xPrxBa0.5CoO3-δ, x = 0.0, 0.2 and 0.5), as well as Ruddlesden-Popper nickelates (Nd2NiO4 +δ) with O-interstitial defects. The analysis of the evolution of molar surface exchange rates with oxygen partial pressure provides information about the mechanisms limiting the O2-surface reaction, which generally is dissociative adsorption or dissociation-limited. At 700 ◦C in air, the La-Ba cobaltite structures, La0.5-xPrxBa0.5CoO3-δ, feature the most active surfaces (kchem≃0.5-1 10−2 cm.s−1), followed by the nickelate Nd2NiO4 +δ and the La-Sr cobalt ferrites, with kchem≃1-5 10−5 cm.s−1. The diffusion coefficients Dchem are higher for cubic perovskites than for the layered ones. For La0.6Sr0.4Co0.8Fe0.2O3-δ and La0.6Sr0.4Co0.2Fe0.8O3-δ, Dchem is 2.6 10−6 cm2.s−1 and 5.4 10−7 cm2.s−1, respectively. These values are comparable to Dchem = 1.2 10−6 cm2.s−1, observed for La0.5Ba0.5CoO3-δ. The layered structure drastically reduces the O-ion bulk diffusion, e.g. Dchem = 1.3 10−8 cm2.s−1 for the Pr0.5Ba0.5CoO3-δ double perovskite and Dchem≃2 10−7cm2.s−1 for Nd2NiO4 +δ. Finally, the analysis of the time evolution of the electrodes shows that the surface cation segregation affects both the O-ion bulk diffusion and the surface exchange rates.